Gender Diversity in Top Management and Its Influence on Stakeholder Lawsuits in Thailand - Wonlop Writthym Buachoom; Muttanachai Suttipun (Asian Journal of Business and Accounting, 2025)
Abstract Manuscript type: Research paper Research aims: This study examines the influence of female top management on managing risk and on the potential for stakeholder lawsuits against listed firms on the Stock Exchange of Thailand (SET). Design/Methodology/Approach: In this study, female top management is defined as a woman in the CEO role, and stakeholders refer primarily to shareholders and employees. Data from 2020 to 2022 were collected from the annual reports of the Top 100 Thai-listed firms. At the same time, a proxy of corporate lawsuits is used to measure and disclose the frequency of lawsuits from corporate stakeholders. Descriptive analysis, correlation matrix, and multiple regression are used to analyse the data. Research findings: The average number of stakeholder lawsuits per firm is 5.732, with little yearly difference between 2020 and 2022. In addition, female top management significantly positively influences such lawsuits against top-listed Thai firms. To consider the relationship between board composition and the potential for stakeholder lawsuits, the study also finds a positive impact of board size and the presence of an international board. At the same time, there is a negative relationship between the age of top management and the likelihood of the emergence of stakeholder lawsuits. Originality/Value: The findings of the study demonstrate that agency and stakeholder theories can be used to explain the positive impact of a female CEO on stakeholder lawsuits filed against listed firms in Thailand.
Keywords: Gender Diversity and Inequality